Kualitas Hasil Tas Makrame Berbahan Pelepah Pisang Menggunakan Teknik Makrame - Rosyidina, Widda; Prasetyaningtyas, Wulansari; Anisa, Bonita Paratejasari (Department of Home Economics, Faculty of Engineering, Universitas Negeri Semarang, 2021)
Abstract: The purpose of this study was to determine the quality of the results of bags made from banana fronds using macrame technique. This research method is experimental research, the type of experiment in this study is pure research, namely the experiment of making bags made from banana fronds using macrame technique, in this experiment making bags with 3 models namely models A, B, and C, using the basic ingredients of banana fronds. This research variable uses a single variable that is the quality of a bag made from banana midrib, this variable does not affect or be influenced by other variables. Data collection methods in the researchers' documentation and questionnaire (questionnaire). The data analysis technique uses descriptive percentages. The results of research on bags were tested for quality by 39 respondents. The results of the quality test analysis showed that the overall bag product was very high, with an average value of 87.05% -91.15%. The highest quality studies were found in bag model C with an average value of 91.15%, the criteria were very high, then bag A with an average value of 87.05, and bag B with an average value of 90.00%. The conclusion from this study is that the highest quality is found in the C model bag with a percentage value of 91.15%. Keywords: baggage quality, banana fronds, macrame technique.